Рассказы: перевод с чешского / сост. и послесл. С. Никольского - Чапек Карел (Правда, 1988)
Экземпляры: ф.4 (1988) / Инвентарный номер: 17747 / Цена: 2.00 / Сис.шифр: 84(4/8) / Авт.знак: Ч-19 / ГРНТИ: 17.82 / ББК: 84(4Чех)